ROOTING OF GRAPEVINE ROOTSTOCK HARDWOOD CUTTINGS BY USING ORGANIC FERTILIZER - MONTEGUTI, Denise; BIASI, Luiz Antonio; PERESUTI, Rafael Aparecido; SACHI, Adriana De Toni; OLIVEIRA, Odirlei Raimundo de; SKALITZ, Rebert (Scientia Agraria, 2008)
The preferred type of cutting used for vegetative propagation of grapevine rootstocks which will later be grafted for grape plant production is the hardwood cutting. The objective of this work was to evaluate the influence of organic fertilizer concentrations on rooting of hardwood cuttings in two grape rootstocks, ‘SO4’ and ‘Kober 5BB’. The cuttings were treated with organic fertilizer at concentration of 0, 5 and 10 mL L-1. Twenty mL solution per 280 cm3 plastic tubes containing commercial substrate were applied twice; when the experiment was installed and 30 days later. At 60 days were evaluated the experiment. Organic fertilizer concentration exerted influence on the percentage of rooted cuttings, the higherst percentage of rooted cuttings (95,8%) was obtained with 5 mL L-1 of organic fertilizer. The ‘Kober 5BB’ rootstock presented higher rooting percentage and number of roots per cutting than the ‘SO4’. There was no difference in shooting or dry matter production between the rooststocks with the different concentrations.